The relative stability of remarriages: a cohort approach using vital statistics. - Clarke, Sally Cunningham; Wilson, Barbara Foley (Family Relations, 1994)
A study was conducted to examine the relative stability of remarriages. The data used for this study were gathered from samples of marriage and divorce certificates compiled by the National Center for Health Statistics as part of the national vital statistics system. The findings indicated that of the couples who married in 1972, fewer joint remarriages than first marriages had divorced by 1988. However, these findings were reversed for specific age/sex groupings, for example, men aged between 20 and 24 years. The variations between the age-aggregated and age-specific results took place because couples entering remarriages were older than those embarking on first marriages and because divorce rates decreased with additional age at marriage. Finally, remarriages that ended in divorce ended more quickly than did first marriages.